2019
DOI: 10.3390/vaccines7040148
|View full text |Cite
|
Sign up to set email alerts
|

The Immunomodulatory Effect of IrSPI, a Tick Salivary Gland Serine Protease Inhibitor Involved in Ixodes ricinus Tick Feeding

Abstract: Ticks are the most important vectors of pathogens affecting both domestic and wild animals worldwide. Hard tick feeding is a slow process—taking up to several days—and necessitates extended control over the host response. The success of the feeding process depends upon injection of tick saliva, which not only controls host hemostasis and wound healing, but also subverts the host immune response to avoid tick rejection that creates a favorable niche for the survival and propagation of diverse tick-borne pathoge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 76 publications
1
29
0
1
Order By: Relevance
“…Indeed, to successfully feed and transmit TBD agents, ticks have to overcome serine protease-mediated host defense pathways that are tightly controlled by tick inhibitors, including Kunitz-type inhibitors such as IrSPI [ 30 ]. In fact, we have previously demonstrated that IrSPI silencing leads to a decrease in the amount of blood ingested by ticks [ 28 ], that the native protein is found in tick saliva and is recognized by the serum of tick-infested rabbits, and that its recombinant form is able to decrease T-cell proliferation in mouse splenocytes [ 31 ]. Similarly, the inflammatory response is a major host defense pathway that ticks must evade to complete feeding and transmit pathogens [ 22 ], and IrLip1, whose RNA is present in tick salivary glands during feeding [ 28 ], may similar to other tick lipocalins be presumed to play a role in evasion of the host response through the sequestration of histamine, which is released at the tick-feeding site [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, to successfully feed and transmit TBD agents, ticks have to overcome serine protease-mediated host defense pathways that are tightly controlled by tick inhibitors, including Kunitz-type inhibitors such as IrSPI [ 30 ]. In fact, we have previously demonstrated that IrSPI silencing leads to a decrease in the amount of blood ingested by ticks [ 28 ], that the native protein is found in tick saliva and is recognized by the serum of tick-infested rabbits, and that its recombinant form is able to decrease T-cell proliferation in mouse splenocytes [ 31 ]. Similarly, the inflammatory response is a major host defense pathway that ticks must evade to complete feeding and transmit pathogens [ 22 ], and IrLip1, whose RNA is present in tick salivary glands during feeding [ 28 ], may similar to other tick lipocalins be presumed to play a role in evasion of the host response through the sequestration of histamine, which is released at the tick-feeding site [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Paris, France. Both recombinant proteins were expressed and purified as previously described for IrSPI [ 31 ]. Briefly, the open reading frames (ORF) of IrSPI and IrLip1 lacking the 5′ sequence encoding their signal peptide (MKATLVAICFFAAVSYSMG and MGLQYALLFACVAAEEVWA, respectively) were synthetized (Eurofins Scientific) as fusion proteins with sequences encoding Twin-Strep-Tag and enterokinase.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Iris was found to suppress T cell proliferation, promote a Th2-type response, and bind to monocytes/macrophages, inhibiting their ability to secrete proinflammatory cytokines IL-6 and TNF-α (150). Similarly, IrSPI suppressed proliferation of CD4 + T lymphocytes and proinflammatory cytokine secretion (Figure 3) from splenocytes and macrophages (151). The Iris homolog Ipis-1 inhibited cellular proliferation and the production of IFN-γ in bovine peripheral blood mononuclear cells, suggesting that Ipis could directly interact with T cells and inhibit their functions (149).…”
Section: Cell-mediated Immunitymentioning
confidence: 93%
“…The deregulation of proteases is a triggering factor for the onset of various pathologies and recent research has pointed out protease inhibitors as promising pharmacological agents [ 13 , 14 ]. Antioxidant, anti-inflammatory, immunomodulatory, antiviral, antimicrobial and antiparasitic activities of these molecules have been demonstrated [ 15 , 16 , 17 , 18 ]. Sangenito et al [ 19 ] reported that inhibitors of HIV aspartyl peptidase affected the integrity of cellular structures of T. cruzi trypomastigotes, leading to metabolic disorders.…”
Section: Introductionmentioning
confidence: 99%